Increased lymphocyte apoptosis in mouse models of colitis upon ABT‐737 treatment is dependent upon BIM expression. (19th May 2015) - Lutz, C.; Mozaffari, M.; Tosevski, V.; Caj, M.; Cippà, P.; McRae, B. L.; Graff, C. L.; Rogler, G.; Fried, M.; Hausmann, M.
Summary Exaggerated activation of lymphocytes contributes to the pathogenesis of inflammatory bowel disease (IBD). Medical therapies are linked to the BCL‐2 family‐mediated apoptosis. Imbalance in BCL‐2 family proteins may cause failure in therapeutic responses. We investigated the role of BCL‐2 inhibitor ABT‐737 for lymphocyte apoptosis in mice under inflammatory conditions. B.6129P2‐interleukin (IL)‐10tm1Cgn/J (IL‐10−/−) weighing 25–30 g with ongoing colitis were used. Fifty mg/kg/day ABT‐737 was injected intraperitoneally (i.p.). Haematological analyses were performed with an ADVIA 2120 flow cytometer and mass cytometry with a CyTOF 2. Following i.p. administration, ABT‐737 was detected in both spontaneous and acute colitis in peripheral blood (PBL) and colon tissue. Treatment led to lymphopenia. CD4+CD44+CD62L+ central memory and CD8+, CD44+ CD62L− central memory T cells were decreased in PBL upon ABT‐737 compared to vehicle‐receiving controls. Increased apoptosis upon ABT‐737 was determined in blood lymphocytes, splenocytes and Peyer's patches and was accompanied by a decrease in TNF and IL‐1B. ABT‐737 positively altered the colonic mucosa and ameliorated inflammation, as shown by colonoscopy, histology and colon length. A decreased BIM/BCL‐2 ratio or absence of BIM in both Bim−/− and Il10−/− × Bim−/− impeded the protective effect of ABT‐737. The BIM/BCL‐2 ratio decreased with age and during the course of treatment. Thus, long‐term treatment resulted in adapted TNF levels and macroscopic mucosal damage. ABT‐737 was efficacious in diminishing lymphocytes and ameliorating colitis in a BIM‐dependent manner. Regulation of inappropriate survival of lymphocytes by ABT‐737 may provide a therapeutic strategy in IBD.